2022
DOI: 10.1186/s40104-022-00692-5
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal bacteria lipopolysaccharides: an immunological and microbial outlook

Abstract: Lipopolysaccharides (LPS) are outer membrane components of Gram-negative bacteria made of three regions: the O-antigen; the core oligosaccharide; and a glucosamine disaccharide linked to hydroxy fatty acids, which is named lipid A. The number phosphate groups, and hydroxy fatty acid chains is associated with the immunopotency and the immunomodulatory activity of LPS, where six-acyl chain lipid A with two phosphate groups is found in virulent strains and five- or four-acyl chain lipid A with one phosphate group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Bacillota) and class Clostridia [ 11 ], although it was previously classified in class Negativicutes. Megasphaera is one of a few genera within its phylum to have a porous pseudo-outer membrane that results in a negative Gram-staining reaction, although details of its lipopolysaccharide structure remain sketchy [ 12 ]. Within the the genus Megasphaera are included several species as follows: M. elsdenii, M. hominis , M. cerevisiae , M. micronuciformis , M. paucivorans and M. sueciensis , which have been isolated from various sources, including the rumen, human clinical specimens, and spoiled beer [ 13 ].…”
Section: Classification and Morphologymentioning
confidence: 99%
“…Bacillota) and class Clostridia [ 11 ], although it was previously classified in class Negativicutes. Megasphaera is one of a few genera within its phylum to have a porous pseudo-outer membrane that results in a negative Gram-staining reaction, although details of its lipopolysaccharide structure remain sketchy [ 12 ]. Within the the genus Megasphaera are included several species as follows: M. elsdenii, M. hominis , M. cerevisiae , M. micronuciformis , M. paucivorans and M. sueciensis , which have been isolated from various sources, including the rumen, human clinical specimens, and spoiled beer [ 13 ].…”
Section: Classification and Morphologymentioning
confidence: 99%
“…Another two species linked to ZnO-free herds were M. elsdenii and Acidaminococcus fermentans . Previous studies have also reported the negative impact of ZnO on the abundance of these two species ( Pieper et al., 2020 ; Silva et al., 2021 ; Ortiz Sanjuán et al., 2022 ), which are capable of produce butyrate from lactate and glutamate, respectively ( Tsukahara et al., 2006 ; Sarmikasoglou and Faciola, 2022 ; Böck, 2009 ). Both amino-acid fermenting species are common members of the adult pig fecal microbiota and increase in the abundance as the animal grows.…”
Section: Discussionmentioning
confidence: 94%
“…The change of rumen microbes has an important relationship with the body’s immune regulation, disease resistance, and animal growth ( Wang et al, 2021 ). Lachnospiraceae_NK4A136_group and Lachnospiraceae_ND3007_group belong to the Lachnospiraceae family, and many microorganisms can produce butyric acid, which can inhibit inflammation and enhance the integrity of the epithelial barrier and are positively correlated with IgG and IgM ( Meehan and Beiko, 2014 ; Sarmikasoglou and Faciola, 2022 ). In addition, Ruminococcus may inhibit inflammation and promote growth in animals through butyrate production ( Scaldaferri et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%